Efeito da idade relativa no futebol: o estudo de caso do Sao Paulo Futebol Clube - Massa, M.; Caldas Costa, E.; Moreira, A.; Thiengo, C. R.; Lima, M.; Quispe, W.; Saldanha Aoki, M. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2014)
The aim of this study was to compare the birth-date distribution of youth athletes of a high-level Brazilian soccer club with the general population of the same age group. In a cross-sectional study, the birth date of 341 youth athletes (under 10-20) was compared with a reference population (live births that occurred in São Paulo state in the same age group; n = 5,480,868). The subjects were divided into quarters of birth: 1st = January-March; 2nd = April-June; 3rd = July-September; 4th = October-December. The chisquare test (?2) was used to compare the expected (reference population) and observed (athletes) distributions. It was detected a significant difference between the expected distribution and observed distribution (?2= 29.53; p<0.0001), with a higher percentage of athletes born in the 1st quarter (47.5%) and a lower percentage in the 4th quarter (8.8%). The present results confirm the occurrence of the relative age effect (RAE) during the player selection process in a top-level Brazilian soccer club. The occurrence of this phenomenon during the selection and development of young athletes needs to be taken into account and should be analyzed carefully in order to minimize the loss of potential youth soccer talent. Further studies are required to identify the determinants of RAE and to establish preventive strategies that ensure a more efficient selection process of young soccer players.